ASSESSMENT OF COMMUNITY PHARMACIST AWARENESS ON ADVERSE DRUG REACTION (ADR) AND PHARMACOVIGILANCE REPORTING SYSTEM IN KHARTOUM LOCALITY, SUDAN - Saeed, Ali Awadallah; Umballi, Osman; Ahmed, Namareg; Ali, Shaza; Alfaki, Azza (Universal Journal of Pharmaceutical Research, 2021)
Introduction: Adverse drug reactions resulting from the use of a medicinal product and were harmful or unpleasant reaction. Pharmacovigilance is related pharmaceuticals product after marketing and associated with collection, detection, assessment, monitoring and prevention of adverse effects. The aim of study is to recognize the awareness of pharmacists regarding pharmacovigilance and adverse drug reactions reporting. Methodology: Descriptive cross-sectional study conducted to 237 pharmacists working in Khartoum’s locality pharmacies from August 2019 to March 2020 selected by simple randomization. The data were collected by face to face interview using self-administrated Questionnaire and analyzed by SPSS version 23. Results: 57.4% from the total sample size never seen adverse drug reactions reporting form, 76.4% never receive training on how to report it and only 10.5% from the pharmacists in the study report it to pharmacovigilance center. 79% from pharmacists in the study were not aware about existence of pharmacovigilance program in Sudan. 51.5 % from pharmacists have good attitude about adverse drug reactions and pharmacovigilance in Sudan while 48.5% had poor attitude. Difficulty in communicating with pharmacovigilance centre in Sudan and how to write the report were the factors discourage pharmacists from reporting of adverse drug reactions. Conclusion: Community pharmacists have insufficient knowledge about the concept of pharmacovigilance and spontaneous ADRs reporting while they had positive attitudes toward pharmacovigilance, despite their little experience with ADRs reporting, this can be strengthened by educational trainings and workshops. Peer Review History: Received: 1 August 2021; Revised: 6 September; Accepted: 14 October; Available online: 15 November 2021 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewers: Dr. Muhammad Zahid Iqbal, AIMST University, Malaysia, drmmziqbal@gmail.com Dr. Olanrewaju Rita-Marie Awotona, Legacy University, Banjul , The Gambia, olanrewajuadegbola@gmail.com